Decontamination and Decommissioned Small Nuclear AIP Hybrid Systems Submarines - Guangya Liu; Daping Qiu (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Being equipped with small reactor AIP is the trend of conventional submarine power in 21st century as well as a real power revolution in conventional submarine. Thus, the quantity of small reactor AIP Submarines is on the increase, and its decommissioning and decontamination will also become a significant international issue. However, decommissioning the small reactor AIP submarines is not only a problem that appears beyond the lifetime of the small reactor nuclear devices, but the problem involving the entire process of design, construction, running and closure. In the paper, the problem is explored based on the conception and the feasible decommissioning and decontamination means are supplied to choose from. DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.3545